2015
DOI: 10.1007/s10103-015-1819-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of experimental tendinitis in rats treated with laser and platelet-rich plasma therapies by Raman spectroscopy and histometry

Abstract: The objective of this controlled experimental study was to analyze the changes in the Achilles tendons of rats with experimentally induced tendinitis after treatment with platelet-rich plasma (PRP) and/or laser therapies by histometry to quantify fibroblasts and by Raman spectroscopy to determine the biochemical concentration of collagen types I and III. Fifty-four male Wistar rats were divided into six treatment groups: control (G1); PRP only (G2); irradiation with 660 nm laser (G3); irradiation with 830 nm l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Overall, when applied to tendon ruptures, blood‐derived products induce an acceleration of the initial phases of tendon healing with reduced inflammation and improved cell proliferation/neovascularization, while these parameters tend to be similar between experimental and control groups at the final follow up [47, 65, 76, 117]. Seven studies concerning collagenase‐induced tendinopathy showed improvements in terms of fibers organization [17, 26, 45, 119], fibers dimension and neovascularization [26], overall histological appearance [20, 45, 119], while one study did not identify any effect of PRP treatment compared to platelet‐derived growth factor‐BB or steroids [100]. Increased cellularity was observed early after treatment in one study [17].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, when applied to tendon ruptures, blood‐derived products induce an acceleration of the initial phases of tendon healing with reduced inflammation and improved cell proliferation/neovascularization, while these parameters tend to be similar between experimental and control groups at the final follow up [47, 65, 76, 117]. Seven studies concerning collagenase‐induced tendinopathy showed improvements in terms of fibers organization [17, 26, 45, 119], fibers dimension and neovascularization [26], overall histological appearance [20, 45, 119], while one study did not identify any effect of PRP treatment compared to platelet‐derived growth factor‐BB or steroids [100]. Increased cellularity was observed early after treatment in one study [17].…”
Section: Resultsmentioning
confidence: 99%
“…27 These growth factors promote the growth of type III collagen, the predominant form of collagen found during the initial reparative phase of tendon healing, as well as type I collagen that is found predominantly in mature tendon. 82,83 Leukocytes in PRP facilitate tissue repair by clearing damaged tissue and releasing growth factors. 84 PRP has been shown to increase anabolic gene expression in tendons and ligaments.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…They also release a variety of growth factors including platelet‐derived growth factor, transforming‐growth factor beta, and vascular endothelial growth factor that stimulate cell proliferation and angiogenesis 27 . These growth factors promote the growth of type III collagen, the predominant form of collagen found during the initial reparative phase of tendon healing, as well as type I collagen that is found predominantly in mature tendon 82,83 . Leukocytes in PRP facilitate tissue repair by clearing damaged tissue and releasing growth factors 84 .…”
Section: Platelet‐rich Plasma Injectionsmentioning
confidence: 99%
“…69 In equine tendons, age-related changes in post-translational glycation of collagen were detected and likely correlated to decline in function. 70 RS application has been described useful in the studies regarding experimental tendinitis, 71 tendon injuries, 72 or degenerative lesions of the supraspinatus RCT. 73 In the combined magnetic field, some studies dealt with periodontal ligament changes during orthodontic treatments 74,75 or in mandibular reconstruction.…”
Section: Tendon and Ligamentsmentioning
confidence: 99%
“…RS application has been described useful in the studies regarding experimental tendinitis, 70 tendon injuries, 71 or degenerative lesions of the supraspinatus RCT. 72 In the combined magnetic field, some studies dealt with periodontal ligament changes during orthodontic treatments 73 , 74 or in mandibular reconstruction.…”
Section: Raman Studies Of Skeletal Tissuesmentioning
confidence: 99%